Psychology of newly married couples in Indonesia: Is it possible to choose childfree by choice or face the gossip of society and family? - Daulay, Harmona; Widyarti, Eka Silvia; Ismail, Rizabuana; Saladin, Tengku Ilham (International Journal of Innovative Research and Scientific Studies, 2023)
This research was about the phenomenon of Childfree by Choice (CBC) in married couples in Indonesia by viewing their diversity, process, consequence, and child values. It used the concepts of diversity (background), process (the process of determining CBC), and consequences (the consequences of CBC). It described various backgrounds, reasons, enabling factors, and consequences for urban married couples who decide to apply for CBC in Indonesia. The research used a qualitative research method with a descriptive approach. The data were collected by distributing questionnaires, developing rapport, and conducting interviews with 15 informants. The result of the research showed that in the stage of diversity (background), the majority of the informants were males, employees of private companies, had gotten married for 5 to 10 years, were Muslims, Javanese, S1 (undergraduate degree) graduates, and had earnings of Indonesian Rupiah IDR 10,000,000 to IDR 15,000,000. Most of them gave the reasons that they cared for the negative effects on the environment, which could cause overpopulation and the scarcity of natural resources, and that it is a choice and the right whether a person wants to have children or not. In this stage of the process, there were some considerations in terms of economic condition, health, occupation, etc. During the subsequent phase, it becomes evident that the decision to pursue childlessness by choice (CBC) yielded favorable outcomes, as individuals did not encounter adverse reactions or societal disapproval about their choice. This observation suggests a notable transformation in societal attitudes towards the notion of parenthood.